Electrostatic interaction driven gold nanoparticle assembly on three-dimensional triangular pyramid DNA nanostructures. (15th August 2017) - Song, Jaejung; Park, Sungmin; Kim, Sehwan; Im, Kyuhyun; Park, Nokyoung
Abstract : The electrostatic attraction between DNA structures and AuNPs has shown nonspecific assembly behavior and allowed tunable plasmonic absorption peaks. Abstract : Here we show that well-defined three dimensional DNA nanostructures can be synthesized from branched DNAs via hybridization and enzymatic ligation. The fabricated triangular pyramid DNA has been employed as a template for assembly of AuNPs. The electrostatic attraction between DNA structures and AuNPs has shown nonspecific assembly behavior and allowed the plasmonic absorption peaks of the assembled nanocomposites to be tuned from visible to near infrared by simple control of the mixing ratio.